ANALISIS RANTAI NILAI UNTUK MENINGKATKAN PENJUALAN PADA DISTRO SCREAMOUS - Merita Bernik; Tamara Nur Wulan Gunawan (Politeknik APP Jakarta, 2018)
The era of free trade spurred causing intense competition among companies. Competition can be based on quality, price or provide more value for its customers. Distro Screamous is a retail company enganged in the apparel industry. To get a more Distro Screamous must have a competitive advantage, one of them by analyzing the value chain in Distro Screamous. The method used is descriptive method is a method of research by collecting data systematically and accurately describe the implementation of the value chain analysis in Distro Screamous. Data collection techniques used by interview, observation and kuesioner. Kuesioner using non probability sampling methods. Based on the results of the implementation of value chain research in Distro Screamous has been good to have an average value of 4.18. However, there are some in the implementation of the value chain that was below the average of them: Infrastructure Company, Human Resources and Operations. In the implementation of the value chain Distro Screamous has several problems that must be faced that Distro Screamous to make efforts to improve the implementation of the value chain.